2017
DOI: 10.1080/08977194.2018.1428966
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inhibition of BMP1-3 decreases progression of CCl4-induced liver fibrosis in rats

Abstract: Liver fibrosis is a progressive pathological process resulting in an accumulation of excess extracellular matrix proteins. We discovered that bone morphogenetic protein 1-3 (BMP1-3), an isoform of the metalloproteinase Bmp1 gene, circulates in the plasma of healthy volunteers and its neutralization decreases the progression of chronic kidney disease in 5/6 nephrectomized rats. Here, we investigated the potential role of BMP1-3 in a chronic liver disease. Rats with carbon tetrachloride (CCl)-induced liver fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 58 publications
(75 reference statements)
0
25
2
Order By: Relevance
“…It has the property of metal protease (matrix metalloproteinases) cutting the COOHterminal of precollagen type I, precollagen type II, and precollagen type III, leading to the maturation of collagens and deposition of the ECM (7,10,12,15). Grgurevic et al (8) reported that BMP1 promotes the cleavage of procollagen type I, resulting in collagen deposition in cirrhosis. In addition, it has also been reported that in the rat model of CKD, BMP1-3 (BMP1 splicing subtype) can promote renal fibrosis by increasing ECM deposition, which was attenuated by specific polyclonal antibody against BMP1ϪBMP3 (9).…”
Section: Introductionmentioning
confidence: 99%
“…It has the property of metal protease (matrix metalloproteinases) cutting the COOHterminal of precollagen type I, precollagen type II, and precollagen type III, leading to the maturation of collagens and deposition of the ECM (7,10,12,15). Grgurevic et al (8) reported that BMP1 promotes the cleavage of procollagen type I, resulting in collagen deposition in cirrhosis. In addition, it has also been reported that in the rat model of CKD, BMP1-3 (BMP1 splicing subtype) can promote renal fibrosis by increasing ECM deposition, which was attenuated by specific polyclonal antibody against BMP1ϪBMP3 (9).…”
Section: Introductionmentioning
confidence: 99%
“…To further study the antifibrotic effect of PC-DCN liposomes, we used rat HSC-T6 astrocytes stimulated with TGF- β to yield active HSC-T6 cells. TGF- β 1, a powerful fibrillary cytokine, stimulates collagen type I expression in primary HSCs [ 15 ]. As shown in Figure 2 , EdU analysis indicated that PC-DCN could significantly inhibit the TGF- β -induced proliferation of HSC-T6 cells ( Figure 2(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with anti-BMP1-3, an isoform of BMP1, decreased CCl 4 -induced rat liver fibrosis, evidenced by downregulated ECMs (e.g., collagen type I) and decreased plasma levels of TGF-β1. 27 In comparison to non-cancerous liver fibroblasts (NFs), BMP4 was found up-regulated in cancer-associated fibroblasts (CAFs), which expressed more ECM genes such as ACTA2 (smooth muscle actin alpha 2) and COL1A1 (alpha-1 type I collagen). In addition, overexpression of BMP4 in fibroblasts showed the phenotype and function of CAFs.…”
Section: Bmps With Pro-fibrotic Effectsmentioning
confidence: 99%